2019
DOI: 10.9734/sajsse/2018/v2i326570
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Socio-economic Factors and Profitability of Hybrid Maize Production in Eastern Terai of Nepal

Abstract: The study was conducted to analyze the socioeconomic factors and profitability of hybrid maize production in eastern Nepal. A household survey was conducted from March to April, 2017 in two districts Morang and Sunsari to collect information on socioeconomic characteristics and economics of maize production. The Structured questionnaire was administered to 98 randomly selected households from two districts i.e. 41 from Morang and 57 from Sunsari district. Descriptive and statistical tools including multiple re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 6 publications
0
6
1
Order By: Relevance
“…However, the farm size was negatively signed and not statistically significant. The result was found different to a study in Eastern Terai of Nepal where the farm size was positive but not significant (Adhikari et al, 2018). The coefficient of education of household head was positive and statistically significant at 5% level.…”
Section: Identification Of Socioeconomic Factors Influencing Both Hybcontrasting
confidence: 99%
See 2 more Smart Citations
“…However, the farm size was negatively signed and not statistically significant. The result was found different to a study in Eastern Terai of Nepal where the farm size was positive but not significant (Adhikari et al, 2018). The coefficient of education of household head was positive and statistically significant at 5% level.…”
Section: Identification Of Socioeconomic Factors Influencing Both Hybcontrasting
confidence: 99%
“…This indicates that for each year increase in the level of education, the production of maize increased significantly. Education enhances the ability of decision makers by enabling the farmers to think critically and use information sources efficiently (Adhikari et al, 2018). Similarly, a study in Tanzania found that education level had statistically impact on maize yield (Justin, 2015).…”
Section: Identification Of Socioeconomic Factors Influencing Both Hybmentioning
confidence: 98%
See 1 more Smart Citation
“…To estimate the socioeconomic factors influencing the lentil production, multiple regression model was used. Adhikari et al (2018) have used the multiple regression model to estimate the factors determining hybrid maize production. Multiple linear regression analysis is an extension of simple linear regression analysis, used to assess the association between two or more independent variables and a single continuous dependent variable.…”
Section: Multiple Regression Modelmentioning
confidence: 99%
“…The rice productivity (yield) was used as dependent variable whereas different socio-economic and demographic characteristics of the respondents were used as explanatory variables. Multiple regression models have been used in several studies to assess the factors affecting the crop yield (Adhikari et al, 2018;Subedi et al, 2020;Bhattarai et al, 2020). The multiple regression model specified in this study is, Y (rice yield) = f (age of the household head, gender of the household head, primary occupation of the household head, number of family members involved in agriculture, livestock standard unit, membership of any organization, subsidy from the government in inputs, area of rice cultivated land) Also, LnY = α0 + βiXi + ei Where; LnY = Rice yield (in natural log form) α0 = Constant βi = Coefficient Xi = Explanatory variables ei = Error term…”
Section: Assessment Of the Factors Affecting The Rice Productionmentioning
confidence: 99%